The Mediating Role of Brand Trust in Business Model Innovation and Brand Loyalty---A Case Study of Guizhou Hot Spring Health Tourism Industry in China - Xue, Xinyu; Chansom , Nakamol; Sirichareechai, Worapoj (Journal of Roi Kaensarn Academi, 2024)
Studying the factors affecting customer brand trust(BT) and brand loyalty(BL) can provide some directions and strategies for merchants to develop and enhance brand loyalty.Based on Guizhou hot spring hotel in china as an example, we studies the influence relationship between different business models (novel business model and efficiency business model) and brand trust and brand loyalty, and studies the intermediary effect relationship of brand trust in the influence of novel business model and efficiency business model on brand loyalty. Previous literature research framework and cross-sectional research survey methods were used to study the proposed hypothesis. A total of 305 questionnaires were collected from the users of Guizhou hot spring hotel. Data were analyzed by SPSS27.0 and AMOS26.0 software, and the relationship between them was tested by the structural equation model. The results show that novel business model and efficient business model have significant positive effects on brand trust and brand loyalty, and brand trust has significant intermediary effects in the influence of different business models (novel business model and efficient business model) on brand loyalty.